Opportunity to learn about disciplinary literacy in senior secondary English classrooms in New Zealand. Issue 2 (2nd April 2016) - Wilson, Aaron; Madjar, Irena; McNaughton, Stuart
ABSTRACT: The New Zealand education system is recognised internationally for its overall high quality. At the same time, there is a persistent gap in achievement between students in low socio‐economic status (SES) schools in which there is an over‐representation of Māori and Pasifika students, and students in more affluent communities. In this paper, we present the findings of a study that explored the participation and achievement rates of secondary school students in selected literacy standards, and used classroom observations to record practices and resources used in literacy teaching. Our findings show the extent to which unequal opportunities to learn (OTLs) for Māori and Pasifika and other students from low SES communities exist at the systems level as well as at the level of classroom instructional offerings. We discuss the factors specific to the New Zealand curriculum and assessment systems that contribute to the current situation and suggest possible ways to achieve a more equitable outcome for all students.